Combined impact of CHCHD10 p.Gly66Val and three other variants suggests oligogenic contributions to ALS - YiYing Wang; YuXin Mi; Hui Wang; JingSi Jiang; Le Mao; YanXi Heng; XiaoGang Li; Min Deng (Frontiers in Neurology)
IntroductionAmyotrophic lateral sclerosis (ALS) is a severe neurodegenerative disease characterized by a progressive loss of motor neurons and muscle atrophy. Genetic factors are known to play important roles in ALS and concomitant presence of rare variants in ALS patients have been increasingly reported.MethodsIn order to explore the genetic variants in ALS patients within the context of oligogenic inheritance and to elucidate the clinical heterogeneity observed in these patients, we conducted whole-genome sequencing on 34 familial ALS (FALS) probands.ResultsIn one proband, we identified a CHCHD10 p.Gly66Val variant, along with three additional variants: UNC13A p.Leu1034Val, SUSD1 p.Trp704Ser, and SQSTM1 p.His359del. This patient exhibited a slow disease progression and a prolonged survival duration, consistent with the clinical features of ALS patients with CHCHD10 variants. This suggests that the CHCHD10 p.Gly66Val variant may play a predominant role in shaping the patient's phenotype, while the other variants may primarily contribute to ALS occurrence.DiscussionVariants in CHCHD10 have been found in ALS and other neurodegenerative diseases, exhibiting significant clinical variability. However, the combinatorial effect of CHCHD10 and other ALS-related gene variants has not been fully studied. Our findings suggest that the combined impact of these four variants contributes to this patient's ALS phenotype, distinguishing it from other, less severe neuromuscular disorders associated with CHCHD10 mutations. Overall, this study further supports the oligogenic pathogenic basis of ALS and offers new insights into understanding the intricate clinical presentations associated with CHCHD10 variants.